Molecular targeting of the Aurora-A/SMAD5 oncogenic axis restores chemosensitivity in human breast cancer cells - Opyrchal, Mateusz; Gil, Malgorzata; Salisbury, Jeffrey L.; Goetz, Mathew P.; Suman, Vera; Degnim, Amy; McCubrey, James; Haddad, Tufia; Iankov, Ianko; Kurokawa, Chenye B.; Shumacher, Nicole; Ingle, James N.; et al. (My University, 2017)
Although the majority of breast cancers initially respond to the cytotoxic effects of chemotherapeutic agents, most breast cancer patients experience tumor relapse and ultimately die because of drug resistance. Breast cancer cells undergoing epithelial to mesenchymal transition (EMT) acquire a CD44+/CD24-/ ALDH1+ cancer stem cell-like phenotype characterized by an increased capacity for tumor self-renewal, intrinsic drug resistance and high proclivity to develop distant metastases. We uncovered in human breast tumor xenografts a novel non-mitotic role of Aurora-A kinase in promoting breast cancer metastases through activation of EMT and expansion of breast tumor initiating cells (BTICs). In this study we characterized the role of the Aurora-A/SMAD5 oncogenic axis in the induction of chemoresistance. Breast cancer cells overexpressing Aurora-A showed resistance to conventional chemotherapeutic agents, while treatment with alisertib, a selective Aurora-A kinase inhibitor, restored chemosensitivity. Significantly, SMAD5 expression was required to induce chemoresistance and maintain a breast cancer stem cell-like phenotype, indicating that the Aurora-A/SMAD5 oncogenic axis promotes chemoresistance through activation of stemness signaling. Taken together, these findings identified a novel mechanism of drug resistance through aberrant activation of the non-canonical Aurora-A/SMAD5 oncogenic axis in breast cancer.